Pharmacomechanical catheter thrombolysis for pregnancy-related proximal deep venous thrombosis: prevention of post-thrombotic syndrome. (3rd May 2021) - Paz, Tal; Bloom, Allan; Roth, Batia; Kalish, Yosef; Rottenstreich, Amihai; Elchalal, Uriel; Da'as, Nael; Varon, David; Spectre, Galia
Abstract: Objective: The efficacy of pharmacomechanical catheter-directed thrombolysis (PCDT) in preventing post thrombotic syndrome (PTS) for pregnancy related deep vein thrombosis (DVT) is unknown. Study design: An observational cross section study of women with pregnancy related proximal (femoral/iliofemoral) DVT who underwent PCDT followed by anticoagulation (study group), and women who were treated with anticoagulation alone (control group). Women were evaluated for PTS using the Villalta scale (primary outcome) and VEINES-QOL/Sym questionnaires. Results: Eleven women with iliofemoral DVT underwent PCDT, two during their first trimester and nine postpartum; 18 women were treated with anticoagulation only. There were no significant differences in age, number of previous pregnancies, and duration of anticoagulation or thrombophilia between the groups. The time between DVT diagnosis and study inclusion was longer in the study group [median 50.5 (range 16–120) months] compared to the control group [median 27 (range 11–64) months], p = .4. None of the women in the PCDT group developed PTS, compared to six (33.3%, p = .03) in the control group, four of whom developed severe PTS. One patient in each group developed recurrent DVT, and one patient in the study group developed a calf hematoma. A reduced frequency of lower extremity symptoms was observed in the PCDT group (VEINES-Sym questionnaire), but no differences in quality of life (VEINES-QOL questionnaire) were reported. Conclusion: This study suggests that PCDT may reduce the incidence of PTS in women with pregnancy related proximal DVT. Bullet points: DVT involving the iliofemoral veins and development of post thrombotic syndrome is frequent among pregnant or postpartum women Studies of pharmacomechanical catheter-directed thrombolysis (PCDT) for deep vein thrombosis did not include pregnant or postpartum women In our observational cross section study women who underwent PCDT (mainly in the postpartum period) had reduced frequency of post-thrombotic syndrome compared to women who received anticoagulation only Larger studies are required to confirm the use of PCDT for prevention of PTS in this population